Composition and strain of the pseudomorphic α-phase intermediate layer at the Ga2O3/Al2O3 interface - M. Schowalter; A. Karg; M. Alonso-Orts; J. A. Bich; S. Raghuvansy; M. S. Williams; F. F. Krause; T. Grieb; C. Mahr; T. Mehrtens; P. Vogt; A. Rosenauer; et al. (APL Materials, 2024)
We investigate the composition of α-phase intermediate layers at epitaxial Ga2O3/Al2O3 interfaces using high angle annular dark field scanning transmission electron microscopy. Their presence is considered a general phenomenon as they are observed independent of the growth technique [Schewski et al., Appl. Phys. Exp. 8, 011101]. Samples were grown by plasma assisted molecular beam epitaxy using different growth conditions. Almost independent of these, the quantitative evaluation of the measured intensities gave Ga concentrations of ∼25%. We show that the previously published model, based on a pure α-Ga2O3 interlayer, fails if it is adapted to the measured composition. Density functional theory (DFT) computations were used to overcome the approximations made in this model and suggest that a stabilization of the layer is possible due to the low Ga concentration (≤35%) at which the α-phase is the most stable. Our surface model computations suggest an exchange of Ga atoms at the surface with Al atoms from the underlying substrate as a possible formation mechanism.